“Scientific basis of rational and ecologically safe use of groundwater in irrigation (in the case of sunflower)” - Sh.R.Akhmedov; I.N. Tursunov; M.M.Rajabova; Hakimov Sh.H; Amanova Z.U (Global Scientific Publishing, 2022)
The low temperature of underground water leads to the extension of the vegetation period of plants (for example, sunflower). For example, the growth and development of plants is delayed for 7-15 days. All this ultimately affects the yield and quality of the agricultural crop, the period of ripening of its fruits. As a result, the lowtemperature water-air soil environment of the aeration zone naturally does not ensure the timely dissolution of nutrients and fertilizers. Also, it does not allow them to be fully assimilated by plant root systems in time. Under such conditions, part of the nutrients sinks under the influence of the falling currents of cold water and mixes with the groundwater. On the other hand, a cold water-air-soil environment of 14-18°C is harmful for plants, significantly reducing the rate of growth and development and exposing it to various diseases. All this, in turn, has a negative impact on the productivity and quality of agricultural crops, and the period of ripening of its fruits.
Keywords: aeration zone; irrigation sources; underground water; temperature